Easter Island archaeology : a tribute to Daniel Schávelzon on the 30th anniversary of the Center for Urban Archaeology at the University of Buenos Aires = Arqueologia en Rapa Nui (Isla de Pascua) : homenaje a Daniel Schávelzon a los treinta años del Centro de Arqueología Urbana de la Universidad de Buenos Aires /: a tribute to Daniel Schávelzon on the 30th anniversary of the Center for Urban Archaeology at the University of Buenos Aires = Arqueologia en Rapa Nui (Isla de Pascua) : homenaje a Daniel Schávelzon a los treinta años del Centro de Arqueología Urbana de la Universidad de Buenos Aires. (2016) - Schávelzon, Daniel
No abstract available